Studi Komparatif: Strategi Pemasaran Pariwisata Thailand, Malaysia, dan Singapura - Fauzi, Dani; Marwani, Iga Safa; Ifada, Zuriyat (LPPM STP ARS Internasional, 2024)
This research explores a comparative analysis of tourism marketing strategies used by Thailand, Malaysia and Singapore to improve their competitiveness in the international tourism market. The research aims to identify the key elements of successful marketing strategies and explore how these approaches can inform the improvement of Indonesia's tourism sector. Using the qualitative comparative analysis (QCA) method, data was collected from literature reviews, government reports, and international tourism statistics. The findings show that Thailand excels with its “Thainess” concept that emphasizes niche markets such as ecotourism and health tourism. Malaysia shifted from mass marketing to an emotional and personalized approach under the “Malaysia Truly Asia” brand, while Singapore rejuvenated its appeal through innovative campaigns such as SingapoReimagine and Muslim-friendly initiatives. The study concludes that adapting to global trends, leveraging digital technology, and using integrated communications are essential in improving tourism competitiveness. Future research should focus on data-driven marketing strategies and their impact on sustainable tourism policies, so as to provide insights for Indonesia to develop competitive and sustainable tourism marketing strategies.